Integrasi Program Pencegahan Penyalahgunaan Napza Bersama Civitas Akademika dan Aparat Desa - Rendy Aulia Birkil; Mari Esterilita; Hastin Trustisari (ARDHI : Jurnal Pengabdian Dalam Negri, 2024)
Abuse of Narcotics and Addictive Substances (NAPZA) is a serious problem that threatens the younger generation, including in Cijagang Village, Cikalong Kulon District, Cianjur Regency. In 2023, 20 cases of drug abuse will be recorded, and in 2024 there will be an additional 2 cases through this program. Socialization of Drug Abuse Prevention through School Communities, intervention carried out on January 27 2024. The aim is to provide knowledge and understanding about the dangers of drug abuse. The methods used include social initiation, social assessment, social organizing, intervention planning, social intervention, evaluation and termination. As a result, 38 out of 60 students attended, with an increase in understanding seen from the pre-test and post-test. This shows that students' knowledge and understanding regarding the implementation of Drug Abuse Prevention Socialization has increased significantly so that this activity is considered successful